Opening Pathways to Restorative Justice: Analysis of Parliamentary Debates on Sex Crime Law Reform in Victoria, Australia. (18th August 2021) - Gang, Daye; Loff, Bebe; Naylor, Bronwyn; Kirkman, Maggie
Abstract: This article reveals the trajectory of parliamentary debate on sex crimes over forty years in Victoria, Australia. We aimed to identify what might have led Parliament to support the introduction of restorative justice as an option for some sex crimes. We searched parliamentary records from 1976 to 2016 for debates on law reform for sex crimes that involved adult victims without intellectual disability. It was evident that politicians' debates shifted in their constructs of offenses and victims in ways that appear to have created space to explore restorative justice.